Potential etiological factors in frontal fibrosing alopecia - Maciejewska, Magdalena; Czuwara, Joanna; Dąbrowska, Natalia; Olszewska, Małgorzata; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2022)
Frontal fibrosing alopecia is a variant of lichen planus, leading to permanent hair loss from the frontal hairline. It occurs mainly in postmenopausal women, however, the role of hormonal factors in the pathogenesis of this type of alopecia has not been determined. The coexistence of frontal fibrosing alopecia and autoimmune diseases is observed, e.g., hypothyroidism, rheumatoid arthritis, vitiligo, polymyositis, systemic lupus erythematosus and discoid lupus erythematosus. Considering the possible role of genetic factors, research is underway to identify human leukocyte antigen (HLA) polymorphisms. One of the most studied factors is sunscreen, widely used in cosmetic products. The data available so far in this regard are controversial. Factors raising significant doubts include: the retrospective nature of the research, basing the collected data on the self-assessment of respondents and the lack of specification of the ingredients of these products. In the light of current data, sunscreen components cannot be considered as a factor playing a role in the pathogenesis of frontal fibrosing alopecia. Overestimation of the role of sunscreens in hair loss could lead to unjustified avoidance of their use and contribute to increased incidence of skin cancer.